Le Sénégal dans l’ère de l’information (1996-2006) - Olivier Sagna (Netcom)
Influenced by globalization trends, Senegal made its first steps in the era of information during the decade 1996-2006 characterized by the privatization of the national telecommunication company, the liberalization of the telecommunication sector, the creation of a regulatory agency, connection to the Internet and the launch of mobile telephony. This evolution went along with numerous projects funded by international donors while civil society was advocating mobilization for social and societal challenges be taken in account. Today, ICTs play an increasing role in the economy in terms of wealth creation, but the majority of people have been excluded from the benefit of those opportunities for economic, cultural and social reasons. This situation could only be changed by implementing strong public policies guided by social profitability to correct the pervasive effects of the market logic more sensitive to economic profitability.